Analysis of Business Resource Variables Affecting Insurance Sales (A Study of Insurance Companies Listed on the IDX) - Kevin Alexander Tjubandi; Hardijanto Saroso (Return : Study of Management, Economic and Bussines, 2023)
Business analysis, especially with an objective to encourage company development, is a common thing to do today. However, conducting an integrated analysis of all operational activities is still a new thing. Furthermore, the demand for sustainable business management encourages companies to collect company operational data in a consistent, strategic and sustainable manner. This research will try to find patterns of internal business analysis in the insurance industry. This research was conducted using secondary data from insurance companies listed on the Indonesia Stock Exchange during the period 2017 to 2021. The research analysis used was carried out using E Views ver 10.  Based on the results of the research and discussion, several conclusions can be drawn, as follows: Human resources have a significant influence on sales at insurance companies during the research period. The highest the number of human resources in the company in the area of knowledge, experience can increase the level of sales (sales) of insurance products. The second resources that boost company performance is fixed assets, followed by advertising, training and agent. This key finding is important because the perception of the existence of an insurance agent that should be the focus of the sales team is not proven here. By increasing the skills, experience, and knowledge of employees for better operational tasks, sales planning, product development, this can improve the sales performance of insurance products. The company assets such as IT, software application, and advertising are playing a strategic role. The business trend moves toward onlines commerce. Advertising can form brand awareness and can provide information to consumers, persuade them to achieve company’s sales targets.